Temporal and spatial distribution characteristics of stratospheric aerosols over xinjiang region based on CALIPSO spaceborne lidar observation - ZiWei, Li; Xiangling, Tang (Frontiers in Earth Science, 2022)
Based on level 3 stratosphere aerosol profile data retrieved from CALIPSO during 2007–2018, optical properties of stratospheric aerosols over the Xinjiang China are analyzed. The results are as follows:Firstly, the optical depth of stratospheric aerosol over Xinjiang is considerably higher in spring (0.0006) and summer (0.0009), than in autumn (0.0003) and winter (0.0002). Secondly, the backscattering ratio of stratospheric aerosol particles decreases with the increase of altitude, with the bottom of the stratosphere as the main contributor of the optical depth. Thirdly, for latitudinal distribution (35°–50° north latitude), the backscattering ratio gradually increases from south to north, with an average value that reaches 0.0013 × 10–3 km−1sr−1 at maximum in May and 0.0003 × 10–3 km−1sr−1 at minimum in January, October and December.